Obstacles to Using Distance E-Learning in Light of the Corona Pandemic and Ways to Confront them from the Point of View of Teachers in Karak Governorate - Al-Tarawneh, Kenana Awad (Journal of Educational and Psychological Sciences, 2021)
The current study aimed to identify the obstacles to the use of e-learning in distance education in light of the Corona pandemic from the point of view of teachers in Karak Governorate and ways to confront them. Four fields, and they were applied to a stratified random sample of (392) male and female teachers from the directorates of education in the Karak governorate. The study found that the obstacles to using e-learning in the distance education process in light of the Corona pandemic from the teachers' point of view, It obtained an overall average (3.63 out of 5), that is, it came with a (medium) degree, and at the level of the fields; The “student” domain came first with an average of (3.76), then the curriculum with an average of (3.71), both with a handicap rating (high), the teacher’s field came third with an average of (3.58), and finally the “infrastructure” field with an average of (3.42), both with a degree (medium). It was also found that there were no statistically significant differences in the obstacles to the use of e-learning in distance education due to the variables of gender and educational qualification, and the existence of differences due to the courses in the field of computer and in favor of those who did not receive any course and those who received one course, meaning that the obstacles they have are great. Such as; Determining appropriate ways to reduce these obstacles, by holding training courses for students and teachers on the use of e-learning, introducing immediate reforms to the curriculum and its teaching methods, and completing the provision of e-learning infrastructure to achieve maximum benefit from technology, especially computer ones.
Keywords: Obstacles; E-Learning; Distance Education; Corona Pandemic; Teachers' point of view; Karak Governorate